Review of the tribe Chilocorini Mulsant from Iran (Coleoptera, Coccinellidae) - Amir Biranvand; Wioletta Tomaszewska; Wenjing Li; Vincent Nicolas; Jahanshir Shakarami; Lida Fekrat; Shahram Hesami (ZooKeys, 2017)
The Iranian checklist of the tribe Chilocorini Mulsant, 1846 (Coleoptera: Coccinellidae) is updated. In total, 13 species belonging to four genera (Brumoides Chapin, 1965, Chilocorus Leach, 1815, Exochomus Redtenbacher, 1843, and Parexochomus Barovsky, 1922) are listed from Iran. An identification key to all genera and species currently known from Iran is presented along with illustrations of adult specimens and male genitalia.